Commodity Currencies and Monetary Policy - Michael B. Devereux; Gregor W. Smith (Queen's University, Department of Economics, 2018)
Countries that specialize in commodity exports often exhibit a correlation between the relevant commodity price and the value of their currency. We explore a natural but little-studied explanation for this correlation. An increase in the commodity price leads to increases in the future values of the international differential in policy interest rates. The tightening of expected future monetary policy relative to the US then leads to an immediate appreciation. We show theoretically that this correlation depends on the stance of monetary policy. We then derive a statistical model that embodies this mechanism and test the over-identifying restrictions for Australia, Canada, and New Zealand. For all three countries, controlling for the effect of commodity prices in predicting current and future monetary policy leaves them no significant, remaining role in statistically explaining exchange rates.
Keywords: F31; F41; E52; 330; commodity currency; exchange rate; monetary policy